2021
DOI: 10.1007/s10140-021-01947-w
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios to improve CT head utilization in the emergency department delineated by critical results reporting

Abstract: Purpose Increasing use of advanced imaging in the emergency department (ED) has resulted in higher cost without better outcomes. Our goal was to evaluate the yield of CT head exams by scenario to guide efforts at improving patient selection. Methods We performed a retrospective study at an academic medical center over 4 years (1/1/2014-12/31/2017). The chief complaint, imaging order, and exam result text were obtained for all adult ED encounters. For the 50 most common chief complaints leading to CT head exams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
0
14
2
Order By: Relevance
“…The diagnostic yields in those previous studies were higher than those in our selected population by 10% to 40%. 27,31,38 Our low diagnostic yield also differs from that of a retrospective study of 170 patients referred to a geriatric unit for confusion. 19 That previous study considered confusion, decreased alertness, and seizure, and its diagnostic yield was higher than in our setting: about 18.0% of their 68 patients had an intracranial cause of confusion.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The diagnostic yields in those previous studies were higher than those in our selected population by 10% to 40%. 27,31,38 Our low diagnostic yield also differs from that of a retrospective study of 170 patients referred to a geriatric unit for confusion. 19 That previous study considered confusion, decreased alertness, and seizure, and its diagnostic yield was higher than in our setting: about 18.0% of their 68 patients had an intracranial cause of confusion.…”
Section: Discussioncontrasting
confidence: 67%
“…14 A recent retrospective ED study over 4 years found a high diagnostic yield (9.8%) for head CT performed for AMS, but that rate decreased to 5.3% when considering a disorder of consciousness alone. 38 A recent review of 294 ED patients recommended that neuroimaging be ordered for confused patients with new focal signs, suspected traumatic brain injury, suspected encephalitis, or no identifiable cause for delirium. 27 When their analysis was confined to 280 cases of acute isolated AMS, the diagnostic yield of CT was even lower (3%) than in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of 26 studies, 11 were performed in the ED, 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 3 in the ICU, 20 , 21 , 22 4 in an inpatient unit, 23 , 24 , 25 , 26 and 8 in mixed settings. 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 Fifteen studies were performed in the US, 5 , 10 , 11 , 18 , 20 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 and 4 in Europe 13 , 16 , 21 , 31 ( Table ). The studies were appraised using the Joanna Briggs Institute quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“… 2 , 3 However, in the subgroup analysis of the studies in the US and Europe, the use of CTH in Europe was not different from that in the US despite socialized medicine and presumed fewer medical-legal concerns. Tu et al 5 reported that AMS accounted for the highest frequency of CTH ordered in the ED in a single health system study; 46% of CTH studies were ordered for AMS alone, with a 10% yield. Computed tomography of the head comprised 38% of all CT studies ordered in the ED and 8% of total ED visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation